PENERAPAN MODEL PEMBELAJARAN PJBL (PROJECT BASED LEARNING) SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN MENYUSUN PROPOSAL DI SISWA KELAS Xl SMA NEGERI 5 LUBUKLINGGAU - Jamaludin; Cekman (Linggau Jurnal Language Education and Literature, 2024)
This school action research aims to improve the ability to prepare proposals based on Project Based Learning in Class XI Students of SMA N 5 Lubuklinggau through the Project Based Learning model. The research subjects numbered 35 people consisting of 15 males and 20 females. The method used was the Classroom Action Research (CAR) method by establishing the Project Based Learning (PJBL) learning model. The research was conducted in two cycles. Each cycle was carried out in two meetings consisting of four stages of planning, implementation, observation, reflection. Data collection was carried out using test and non-test techniques. The results of the study showed a significant increase in students' ability to Write Proposals after the implementation of the PBL model. In cycle I, the test results showed an average increase in value of 15%, while in cycle II it increased to 25%. Students also showed an increase in learning motivation and independence in the learning process. Thus, the PBL model has proven effective in improving the ability to Write Proposals.